1998
DOI: 10.1074/jbc.273.29.18185
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Is a Novel Potent Inducer of Connective Tissue Growth Factor Expression

Abstract: Due to its potent effect on fibroblast proliferation and extracellular matrix deposition, connective tissue growth factor (CTGF) seems to play an important role in the pathogenesis of fibrotic disease. Since glucocorticoids are frequently used for the therapy of these disorders, we determined a potential effect of these steroids on CTGF expression. In cultured fibroblasts, a striking induction of CTGF expression was observed after dexamethasone treatment and occurred in a time-and dosedependent manner. This ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
104
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 23 publications
11
104
1
1
Order By: Relevance
“…Among the hormones tested, only dexamethasone significantly increased CTGF transcript levels after long-term treatment and even more impressively within 5 h after a single injection of this steroid (data not shown). A rapid and dramatic induction of CTGF mRNA and protein by dexamethasone has also been observed in cultured fibroblasts and described recently (Dammeier et al 1998). The same authors also reported on dexamethasone induced upregulation of CTGF mRNA levels in heart, kidney and skin of mice that had been injected repeatedly with dexamethasone.…”
Section: Discussionsupporting
confidence: 52%
“…Among the hormones tested, only dexamethasone significantly increased CTGF transcript levels after long-term treatment and even more impressively within 5 h after a single injection of this steroid (data not shown). A rapid and dramatic induction of CTGF mRNA and protein by dexamethasone has also been observed in cultured fibroblasts and described recently (Dammeier et al 1998). The same authors also reported on dexamethasone induced upregulation of CTGF mRNA levels in heart, kidney and skin of mice that had been injected repeatedly with dexamethasone.…”
Section: Discussionsupporting
confidence: 52%
“…In a study in mice CTGF expression was induced by corticosteroids in fibroblasts. 45 In our study, we did not see an increased CTGF expression in corticosteroid-related ON compared to ON due to other causes. However, this could be explained by the time difference of bone cylinder retrieval and corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 54%
“…A unique, specific TGF-␤ response element has been identified in the CTGF promoter that directly induces transcriptional activation of the gene, 17 but expression may also be induced by corticosteroids. 8 CTGF has mitogenic action on fibroblasts 12,22 and can induce the extracellular matrix-associated genes type I colla- gen, fibronectin, and ␣5-integrin. [10][11][12] It modulates cell adhesion in fibroblasts and affects neovascularization.…”
Section: Discussionmentioning
confidence: 99%